2007
DOI: 10.1523/jneurosci.1817-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

The I–II Loop Controls Plasma Membrane Expression and Gating of Cav3.2 T-Type Ca2+Channels: A Paradigm for Childhood Absence Epilepsy Mutations

Abstract: Calcium currents via low-voltage-activated T-type channels mediate burst firing, particularly in thalamic neurons. Considerable evidence supports the hypothesis that overactive T-channels may contribute to thalamocortical dysrhythmia, including absence epilepsy. Single nucleotide polymorphisms in one of the T-channel genes (CACNA1H, which encodes Ca v 3.2) are associated with childhood absence epilepsy in a Chinese population. Because only a fraction of these polymorphisms are predicted to increase channel act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
134
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 32 publications
(34 reference statements)
10
134
1
Order By: Relevance
“…4 A similar result was reported in a functional study of single nucleotide polymorphisms present in childhood absence epilepsy patients (16), where it was observed that the mutation C456S in Ca v 3.2 channels (located in the proximal I-II loop) shifted the voltage dependence of activation to more negative potentials (17). This observation was followed up with a set of deletions exploring the role of the I-II loop in Ca v 3.2 channels (18). This study revealed that the I-II loop has two separable roles: one to regulate surface expression and another to modulate the biophysical properties of Ca v 3.2 channels.…”
supporting
confidence: 77%
“…4 A similar result was reported in a functional study of single nucleotide polymorphisms present in childhood absence epilepsy patients (16), where it was observed that the mutation C456S in Ca v 3.2 channels (located in the proximal I-II loop) shifted the voltage dependence of activation to more negative potentials (17). This observation was followed up with a set of deletions exploring the role of the I-II loop in Ca v 3.2 channels (18). This study revealed that the I-II loop has two separable roles: one to regulate surface expression and another to modulate the biophysical properties of Ca v 3.2 channels.…”
supporting
confidence: 77%
“…The ability of zinc to decrease gating charge 25% is consistent with immobilization of one of the four voltage-sensor paddles. It is interesting to note that repeat I plays a dominant role in the opening of both HVA and LVA channels (37,38). These studies also provide evidence for considerable structural similarity between voltage-gated K ϩ and Ca 2ϩ channels, and combined with the established role of Ca v 3.2 in pain and epilepsy, provide a structural model for the development of novel therapeutics (17,24,39,40).…”
mentioning
confidence: 84%
“…When the phenotypic spectrum was extended to include JAE, JME, and temporal lobe epilepsies, more new variants in CACNA1H were identified in affected individuals. When expressed, several of these variants altered T-type channel properties that would be predicted to augment calcium current (Khosravani et al 2005;Peloquin et al 2006;Heron et al 2007) and increase surface expression (Vitko et al 2007). More recently, when the C456S variant was expressed in neurons, it increased neuronal firing, lowered the threshold for rebound burst firing, and induced changes in gene expression (Eckle et al 2014).…”
Section: T-type Calcium Channel Mutations and Human Epilepsymentioning
confidence: 99%